THE EFFECT OF LAYING AT ROOM TEMPERATURE ON THE PH VALUE AND TOTAL BACTERIA OF BALI BEEF - Rahayu, Ni Putu Tessa Arsaning; Agustina, Kadek Karang; Swacita, Ida Bagus Ngurah (Buletin Veteriner Udayana, 2022)
Bali beef is an ideal medium for the growth of microorganisms, because it is rich in protein, minerals and water. When placed at room temperature, the meat will spoil more quickly. The purpose of this study was to determine the effect of laying beef at room temperature on the pH value and total bacteria. This research method tested 24 pieces of beef with a weight of 10 grams each and placed at room temperature (27-30°C) then tested with pH and total bacteria tests. The research design used was Completely Randomized Design (CRD) with 4 treatments of laying time at room temperature for 0 hours, 3 hours, 6 hours, and 9 hours with 6 replications. The research data were analyzed by means of variance and if the results were significantly different, it was continued with Duncan's test. The results showed that laying beef at room temperature had no effect on the pH value (P>0.05), but had a very significant effect (P<0.01) on increasing total bacteria. It concluded that the quality of bali beef placed at room temperature will reduce the quality